2017
DOI: 10.1158/1535-7163.mct-17-0159
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aurora A and Aurora B Is Required for the Sensitivity of HPV-Driven Cervical Cancers to Aurora Kinase Inhibitors

Abstract: The activity and efficacy of Aurora inhibitors have been reported in a wide range of cancer types. The most prominent Aurora inhibitor is alisertib, an investigational Aurora inhibitor that has been the subject of more than 30 clinical trials. Alisertib has inhibitory activity against both Aurora A and B, although it is considered to be primarily an Aurora A inhibitor Here, we show that alisertib inhibits both Aurora A and B in preclinical models of HPV-driven cervical cancer, and that it is the inhibition of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…They have each been previously reported to be overexpressed in HPV-positive CIN or cancer and some have been evaluated for use as biomarkers [90] , [91] , [92] . Other genes, such as the genes encoding for aurora kinase A and B (AURKA and AURKB), have been implicated as survival signals for HPV-infected cells and inhibition of AURKA/B using Alisertib induced cell death in HPV-transformed cervical cancer cell lines [93] , [94] . It important to note that the utility of this drug was also evaluated in the K14E7 skin grafting model where Alisertib-treated E7-expressing skin grafts displayed increased apoptotic bodies compared to untreated controls [93] .…”
Section: Resultsmentioning
confidence: 99%
“…They have each been previously reported to be overexpressed in HPV-positive CIN or cancer and some have been evaluated for use as biomarkers [90] , [91] , [92] . Other genes, such as the genes encoding for aurora kinase A and B (AURKA and AURKB), have been implicated as survival signals for HPV-infected cells and inhibition of AURKA/B using Alisertib induced cell death in HPV-transformed cervical cancer cell lines [93] , [94] . It important to note that the utility of this drug was also evaluated in the K14E7 skin grafting model where Alisertib-treated E7-expressing skin grafts displayed increased apoptotic bodies compared to untreated controls [93] .…”
Section: Resultsmentioning
confidence: 99%
“…Alisertib treatment of mice bearing HPV + OPC cells successfully inhibited tumour growth but failed to eliminate tumours completely (6). We consider the possibility that alisertib treatment was not effective at eliminating E7 expressing tumours in vivo despite our previous observations that alisertib-mediated killing of HPV + tumours are sensitized to the presence of E7 (5)(6)(7). Owing to our recent success at completely eliminating HPV + cervical cancer tumours in vivo by deleting E7 using CRISPR technology (10), we rationalize that this would occur in HPV + OPC tumours.…”
Section: Resultsmentioning
confidence: 86%
“…High-risk HPV cancers are driven by major HPV oncogenes, E6 and E7, which promote uncontrolled cell growth and genomic instability by down-regulate the tumour suppressor proteins, p53 and retinoblastoma (Rb), respectively (4). Our lab has shown that the presence of HPV E7 sensitizes both HPV + cervical and HPV + OPC tumours to tumour regression by inhibiting aurora kinases (AURKs) using an investigational AURK inhibitor, alisertib (5)(6)(7). AURKs are a group of serine-threonine kinases that regulate cell cycle and are involved in a variety of processes including centrosome maturation, entry in mitosis, microtubule spindle assembly, and cytokinesis (8-9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Aurora A also participates in the regulation of the G2/M phase cell cycle checkpoint; Aurora A overexpression can counter the checkpoint activation induced by DNA damage in the G2/M phase, resulting in genome instability and tumour formation. Increasing evidence has revealed that aberrant Aurora A expression was found in lung adenocarcinoma, liver, colon and breast cancer, and many other malignant tumours (16,17). The overexpression of Figure 5.…”
Section: Discussionmentioning
confidence: 99%